2002
DOI: 10.1023/a:1013651022431
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Degradable copolymers were synthesized by ring opening polymerization of lactide in the presence of poly(ethylene glycol) (PEG), using CaH2 as a biocompatible initiator. The resulting PLA/PEO/PLA triblock copolymers were dissolved in a biocompatible solvent, namely tetraglycol. Physically crosslinked hydrogels were then prepared by introducing small amounts of water into the thus obtained solutions. Hydrolytic degradation of the highly swollen hydrogels was realized in 0.13 M pH=7.4 phosphate buffer, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 3 publications
2
20
0
Order By: Relevance
“…For this reason, the hydrolytic degradation of PLLA-b-PEO-b-PLLA and PDLLA-b-PEP was faster at an early stage than at a late stage. In contrast, Rashkov et al [200] and Li et al [205] reported that the acidic and NHD of PLLA-b-PEO-b-PLLA was not enhanced due to the phase separation between PLLA and PEO segments and that the hydrolyzability of the ester linkage between PEO and PLA in copolymers is similar to that in PLA segments, and therefore PEO segments were not released at an early stage of degradation [208]. Further work is required to elucidate the causes for such a mechanism difference.…”
Section: Molecular Degradation Mechanismmentioning
confidence: 96%
“…For this reason, the hydrolytic degradation of PLLA-b-PEO-b-PLLA and PDLLA-b-PEP was faster at an early stage than at a late stage. In contrast, Rashkov et al [200] and Li et al [205] reported that the acidic and NHD of PLLA-b-PEO-b-PLLA was not enhanced due to the phase separation between PLLA and PEO segments and that the hydrolyzability of the ester linkage between PEO and PLA in copolymers is similar to that in PLA segments, and therefore PEO segments were not released at an early stage of degradation [208]. Further work is required to elucidate the causes for such a mechanism difference.…”
Section: Molecular Degradation Mechanismmentioning
confidence: 96%
“…Interestingly, polyanhydrides degrade more slowly at acidic pH with far more rapid degradation in basic solutions [113,121]. Enzymatic (e.g., proteases) degradation of polymers has been extensively studied [122124]. …”
Section: Modulation Of Geometry Of Polymeric Carriers For Antioxidantsmentioning
confidence: 99%
“…It may be possible that IgG-Fab, IgG and catalase possess very low diffusivity through polymer matrix (due to large molecular weights) and hence their release was mainly controlled by degradation of polymers. As published in previous reports degradation of PCL is very slow (Gou et al, 2010, Frank et al, 2005, Huang et al, 2004, Li et al, 2002, Li et al, 2005) and hence it is anticipated that PB copolymers which are comprised of PCL blocks may also degrade slowly. Due to the slower degradation of PB copolymers, release of IgG-Fab, IgG and catalase followed zero order release for a long time period.…”
Section: Resultsmentioning
confidence: 73%